2019
DOI: 10.1111/jcpt.13062
|View full text |Cite
|
Sign up to set email alerts
|

CYP2C19 phenotype in South‐East Asian Acute Coronary Syndrome patients and impact on major adverse cardiovascular events

Abstract: What is known and objective: Several Caucasian cohort studies have associated at least one loss-of-function CYP2C19 on Clopidogrel (LoF-Clopidogrel) with major adverse cardiovascular events (MACE), and only a couple have used Clinical Pharmacogenetics Implementation Consortium (CPIC ®) phenotype grouping to study the associations. We primarily aimed to study the impact of use of platelet reactivity testing to escalate antiplatelet therapy and secondarily to study the association of CPIC phenotype with MACE out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Our result addresses the knowledge gap for patients in Southeast Asia with CYP2C19 LOF alleles using clopidogrel after PCI. The results are consistent with the Singapore cohort ( 21 ), which revealed that LOF patients were significantly more likely to experience MACE compared to non-LOF subjects in acute coronary syndrome (8.0 vs. 5.4%, p = 0.041). In patients without ACS, another smaller cohort in Malaysia recruited patients who underwent elective PCI ( 20 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our result addresses the knowledge gap for patients in Southeast Asia with CYP2C19 LOF alleles using clopidogrel after PCI. The results are consistent with the Singapore cohort ( 21 ), which revealed that LOF patients were significantly more likely to experience MACE compared to non-LOF subjects in acute coronary syndrome (8.0 vs. 5.4%, p = 0.041). In patients without ACS, another smaller cohort in Malaysia recruited patients who underwent elective PCI ( 20 ).…”
Section: Discussionsupporting
confidence: 89%
“…The relationship between CYP2C19 LOF alleles in patients with AMI using clopidogrel and clinical events has been studied in Northeast Asia, whereas studies in Southeast Asia are limited ( 20 , 21 ). In Taiwan, although the location was near northeast Asian, the island of Southeast Asia (ISEA) ancestry was one of the major genetic ancestries in Taiwan.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 The greater risk of MACE in Asian patients than in white patients was hardly surprising, given that the prevalence of CYP2C19 LoF is almost twice that in Asian than in white populations. 9 In our adjusted model, we also identified additional factors associated with MACE, including baseline LDL, female sex, and history of ACS and ARB use. Notably, every 0.1 mmol/l increase in baseline LDL elevates MACE risk by 89% in our cohort.…”
Section: Discussionmentioning
confidence: 99%